2003
DOI: 10.1104/pp.102.019364
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Xanthophyll Biosynthetic Genes during Light-Dependent Chloroplast Differentiation

Abstract: In higher plants, etioplast to chloroplast differentiation is characterized by dramatic ultrastructural changes of the plastid and a concomitant increase in chlorophylls and carotenoids. Whereas the formation and function of carotenes and their oxygenated derivatives, the xanthophylls, have been well studied, little is known about the regulation of the genes involved in xanthophyll biosynthesis. Here, we analyze the expression of three xanthophyll biosynthetic genes (i.e. ␤-carotene hydroxylase [bhy], zeaxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 64 publications
4
74
1
Order By: Relevance
“…However, the response mechanism may not involve increased flux to ABA because leaf ABA biosynthesis is limited not by the carotenoid precursor pool, but by NCED-mediated conversion of the xanthophyll precursors to ABA (Parry et al, 1990;Marin et al, 1996;Audran et al, 1998;Thompson et al, 2000a). Instead, increased carotenoid flux in leaves may relate to other processes, such as photosynthesis, temperature stress tolerance, and photoprotection (Davison, 2002;Rossel et al, 2002;Woitsch and Romer, 2003;Havaux et al, 2007). Nonstressed embryo, dissected at 20 d after pollination (DAP), contains few accumulated carotenoids, and the most prevalent PSY transcripts were those of PSY2 followed by PSY3; perhaps, in this tissue, which is lacking in photosynthetic plastids, PSY expression could possibly relate to plant development (Sorefan et al, 2003;Booker et al, 2004) and/or apocarotenoid biosynthesis (Matusova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the response mechanism may not involve increased flux to ABA because leaf ABA biosynthesis is limited not by the carotenoid precursor pool, but by NCED-mediated conversion of the xanthophyll precursors to ABA (Parry et al, 1990;Marin et al, 1996;Audran et al, 1998;Thompson et al, 2000a). Instead, increased carotenoid flux in leaves may relate to other processes, such as photosynthesis, temperature stress tolerance, and photoprotection (Davison, 2002;Rossel et al, 2002;Woitsch and Romer, 2003;Havaux et al, 2007). Nonstressed embryo, dissected at 20 d after pollination (DAP), contains few accumulated carotenoids, and the most prevalent PSY transcripts were those of PSY2 followed by PSY3; perhaps, in this tissue, which is lacking in photosynthetic plastids, PSY expression could possibly relate to plant development (Sorefan et al, 2003;Booker et al, 2004) and/or apocarotenoid biosynthesis (Matusova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are synthesized during light exposure, but it was shown that when light intensity increases from 150 to 280 mmol m -2 s -1 the rate of photo oxidation is higher than the rate of synthesis and carotenoids are destroyed, reaching a basal level (Simkin et al, 2003). The level of expression of some carotenogenic genes are reduced following prolonged illumination at moderate light intensities (Woitsch and Römer, 2003), as was shown for pds transcript accumulation in tomato seedlings and was referred to as inhibition by final product (lycopene) (Corona et al, 1996;Giuliano et al, 1993). This phenomenon could also explain the behavior of carrot zds1.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of these studies show that carotenogenic genes are expressed in photosynthetic organs exposed to different light qualities, during the transition of etioplasts to chloroplasts (de-etiolation) (Römer and Fraser, 2005;Bramley, 2002). During these processes, carotenogenic gene expression is mostly regulated at the transcriptional level mediated by photoreceptors, such as the family of phytochromes (PHYA-PHYE), cryptochromes (CRY) and phototropins (Simkin et al, 2003;Woitsch and Römer, 2003;Briggs and Olney, 2001;Scheppens et al, 2004, Franklin et al, 2005Briggs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While most structural genes of the pathway have been characterized (Hirschberg, 2001), very little is known regarding the regulatory network that controls carotenogenesis. The control of carotenoid biosynthesis via the redox status of components of the photosynthetic electron transport has been established during etioplast-tochloroplast transition (Woitsch and Romer, 2003). In earlier studies, the involvement of quinones in carotenoid desaturation was demonstrated biochemically (Mayer et al, 1990) and genetically (Norris et al, 1995).…”
Section: Introductionmentioning
confidence: 99%